Особливості післядипломної освіти сімейних лікарів з питань планування сім’ї та безплідного шлюбу - Авраменко, Наталія Вікторівна; Семененко, Ілона Валентинівна; Сєрих, Катерина Валеріївна; Avramenko, N. V.; Semenenko, I. V.; Sierykh, К. V. (My University, 2019)
Анотація. В статті подано особливості викладання циклу тематичного удосконалення за темою «Безплідний шлюб. Планування сім’ї» для сімейних лікарів. Мета циклу – вдосконалення теоретичних знань щодо безпліддя та забезпечення лікарів загальної практики сучасними знаннями з лікування даної патології та планування сім’ї для підвищення їх професійного рівня надання медичної допомоги. Співробітники кафедри розробили цикл тематичного удосконалення «Безплідний шлюб. Планування сім'ї» для популяризації теоретичних знань з методів діагностики та лікування в практиці сімейного лікаря, підвищення якості лікувально-діагностичної допомоги гінекологічним хворим, покращення професійних навичок і умінь лікарів сімейної медицини. Проведення циклу тематичного удосконалення «Безплідний шлюб. Планування сім'ї» дає змогу доповнити, удосконалити та забезпечити високий рівень підготовки лікарів з питань планування сім'ї та покращення репродуктивного здоров'я населення. Summary. In the modern world, in conditions of poor ecology and many stressful factors, the problem of infertility is extremely urgent. The nature of changing demographics puts the problem of infertile marriage among the most important today in almost all regions of Ukraine. Infertile marriage – the absence of pregnancy in a couple of childbearing age for one year of regular sexual activity without the use of any contraceptive methods. Along with the topic of infertility, family planning matters are important. Centers and information services for family planning inform the population about certain reproductive results, such as preventing an unplanned pregnancy, giving birth to desired children, treating infertility, sex education, counseling on family life. The interaction between doctors of various levels in the provision of medical care predicts a significant improvement in the reproductive health of the population. The article presents the features of teaching a cycle of thematic improvement on the topic "Infertile marriage. Family planning" for family doctors. Explained curriculum and structure of the cycle. The goal of the cycle is to improve theoretical knowledge on infertility and provide general practitioners with modern knowledge on the treatment of this pathology and family planning to increase their professional level of medical care. Employees of the department developed a cycle of thematic improvement “Barren marriage. Family planning ”to popularize theoretical knowledge on the methods of diagnosis and treatment in the practice of a family doctor, improving the quality of medical and diagnostic assistance to gynecological patients, improving the professional skills of family medicine doctors. At the lectures of the course for family medicine doctors “Infertility. Family Planning” pays considerable attention to providing specialists with modern scientific data on qualified counseling on barren marriage and family planning. Conducting a cycle of thematic improvement “Barren marriage. Family Planning” allows you to complement, improve and provide a high level of training for doctors in family planning and improving the reproductive health of the population.
Peculiarities of post-graduate education of family doctors on matters of planning and infertile marriage
Авраменко Н. В. - ORCID: https://orcid.org/0000-0003-4403-2920; Семененко І. В. - ORCID: https://orcid.org/0000-0001-7431-7818; Сєрих К. В. - ORCID: https://orcid.org/0000-0003-1648-7530
Keywords: післядипломна освіта; акушерство; гінекологія; безпліддя; планування сім’ї; сімейна медицина; postgraduate education; obstetrics; gynecology; infertility; family planning; family medicine